2007
DOI: 10.1158/0008-5472.can-07-0266
|View full text |Cite
|
Sign up to set email alerts
|

The Soluble Wnt Receptor Frizzled8CRD-hFc Inhibits the Growth of Teratocarcinomas In vivo

Abstract: Wnt signaling is important for normal cell proliferation and differentiation, and mutations in pathway components are associated with human cancers. Recent studies suggest that altered wnt ligand/receptor interactions might also contribute to human tumorigenesis. Therefore, agents that antagonize wnt signaling at the extracellular level would be attractive therapeutics for these cancers. We have generated a soluble wnt receptor comprising the Frizzled8 cysteine-rich domain (CRD) fused to the human Fc domain (F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 49 publications
5
106
0
1
Order By: Relevance
“…OMP-18R5 did not display activity in colon tumors harboring APC or β-catenin mutations, but was highly active in a colon tumor with wildtype APC and β-catenin. OMP-18R5 also inhibited the growth of the established cell line PA-1 (derived from a human teratocarcinoma), which had previously shown to be inhibited by FZD8-fc protein (12) (Fig. 3F).…”
Section: Wnt Pathway Blockade Inhibits the Growth Of Human Tumor Xenomentioning
confidence: 64%
See 2 more Smart Citations
“…OMP-18R5 did not display activity in colon tumors harboring APC or β-catenin mutations, but was highly active in a colon tumor with wildtype APC and β-catenin. OMP-18R5 also inhibited the growth of the established cell line PA-1 (derived from a human teratocarcinoma), which had previously shown to be inhibited by FZD8-fc protein (12) (Fig. 3F).…”
Section: Wnt Pathway Blockade Inhibits the Growth Of Human Tumor Xenomentioning
confidence: 64%
“…This selectivity relative to potential intracellular signaling components may offer advantages in safety and therapeutic index. Previous studies have indicated that use of soluble Wnt inhibitors and decoy receptor molecules can impact tumor growth (11,12). In this article we demonstrate the ability to generate a potent Wnt inhibitory antibody that functions by binding to select Fzd receptors, and that this antibody is active across a range of human tumor types.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Because the induction of Fzd8 expression during osteoclastogenesis occurs before the (CRD; Fig. 5 E), which can be used to block receptor binding (DeAlmeida et al, 2007;Schulte and Bryja, 2007).…”
Section: Activating Canonical Wnt Signaling In Osteoclast Progenitorsmentioning
confidence: 99%
“…Thus, SFRPs can modulate Wnt signaling by sequestering Wnts through the CRD or by acting as dominantnegative inhibitors, forming inactive complexes with the frizzled receptors (Bovolenta et al, 2008). In addition, engineered SFRP-like proteins such as the soluble CRD of the receptor Frizzled 8 potently inhibit autocrine Wnt signaling and tumor growth in mice carrying teratomas (DeAlmeida et al, 2007).…”
Section: Introductionmentioning
confidence: 99%